Development of a system to control flow of coolant in turning operation / Rajesh Kumar Maurya...[et al.] - M. S., Niranjan; Nagendra, Kumar Maurya; Shashi, Prakash Dwivedi1 (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
Automation of cooling system in machine tools is an effective method for achieving higher productivity and increased tool life. A cooling system is designed to control the operating temperature on the cutting tool tip by circulating coolant through a reservoir built on the top of the machine tool. This arrangement maintains the coolant flow rate as per variation of cutting tool tip temperature sensed by LM-35 temperature sensor which is located 1 cm away (calibrated distance) from the cutting tool tip and whose output voltage is linearly proportional to the temperature. Coolant flow rate is varied in such a manner that the temperature of the cutting tool tip remains within fixed value of temperature. The aim of present work is to develop a cooling control panel system to provide coolant on cutting tool tip in turning operation of mild steel. The coolant flow rate can be increased or decreased as per the variation of sensor temperature during turning of mild steel with high speed steel (HSS) cutting tool at different depth of cut, and spindle speed ,keeping feed rate constant which results in effective cooling of the cutting tool tip. The experiments were carried out with and without use of coolant. It supplies the coolant as per instructions of cooling control panel system which results in saving of coolant as well as power. The mechatronics application of designed cooling control panel system enabled the reduction in cutting tool tip temperature in more robust way as compare to conventional cooling system.